‘What’s Your Story?’ Building Diversity, Equity, and Inclusion - Candice Harrison-Train; Carmel Marock; Sally Field (The Thinker)
Diversity, equity, and inclusion (EDI) are critical issues for leaders, communities, and organisations. Throughout history, telling stories has been a method for people to make sense of their environment, organise experiences and ideas, and communicate with their community to create shared understanding. Heartlines, a South African centre for values promotion, developed ‘What’s Your Story?’ (WYS) – a simple, yet effective initiative to build greater understanding, cohesion, trust, and reconciliation through the sharing of stories. An external evaluation of the programme used a mix of qualitative and quantitative evaluation methods to assess WYS implementation in church communities and workplaces. The study showed strong evidence that being exposed to WYS results in positive changes at the level of the individual, within churches, workplaces or other organisations, and in the wider community. The findings demonstrated that WYS enhanced empathic skills and suggests that this is a useful approach to enhancing appreciation of diversity and building inclusivity.